Deep Learning Techniques to Detect Botnet - Son, Doan Trung; Tram, Nguyen Thi Khanh; Hieu, Pham Minh (Journal of Science and Technology on Information security, 2022)
Abstract— Over the past time, the world has witnessed an unprecedented explosion of Deep Learning. Besides thedevelopment of Information Technology, security and safety threats are also increasing, one of which is the Botnet network. Botnet network is increasingly complex and difficult to detect, and traditional techniques are no longer effective, so one of the urgent problems today is to find an effective solution to detecting botnets [2]. Based on the characteristics of deep learning such as scalability, performance, execution time, interpretability, etc., therefore, in this paper, the author proposes to use deep learning techniques to detect Botnet networks.